2016
DOI: 10.1007/s00270-016-1526-8
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Patient and Staff Radiation Dose Monitoring in IR Practice

Abstract: PurposeKnowledge of medical radiation exposure permits application of radiation protection principles. In our center, the first dedicated real-time, automated patient and staff dose monitoring system (DoseWise Portal, Philips Healthcare) was installed. Aim of this study was to obtain insight in the procedural and occupational doses.Materials and MethodsAll interventional radiologists, vascular surgeons, and technicians wore personal dose meters (PDMs, DoseAware, Philips Healthcare). The dose monitoring system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 16 publications
0
22
0
4
Order By: Relevance
“…Radiation exposure for the patient during image-guided interventional procedures can be considerable, especially due to digital subtraction angiography (DSA), and the implications of radiation are well known [1][2][3]. In addition, the clinical staff performing the procedures is exposed to radiation as well, and the awareness for the radiation impact on the health of the clinical staff has increased over the last decade, resulting in the development real time dose monitoring systems for clinical staff [4]. Especially for patients undergoing repeated procedures, the cumulative radiation dose is even higher [5].…”
Section: Introductionmentioning
confidence: 99%
“…Radiation exposure for the patient during image-guided interventional procedures can be considerable, especially due to digital subtraction angiography (DSA), and the implications of radiation are well known [1][2][3]. In addition, the clinical staff performing the procedures is exposed to radiation as well, and the awareness for the radiation impact on the health of the clinical staff has increased over the last decade, resulting in the development real time dose monitoring systems for clinical staff [4]. Especially for patients undergoing repeated procedures, the cumulative radiation dose is even higher [5].…”
Section: Introductionmentioning
confidence: 99%
“…This could be argued because a similar result for patients and operators with regard to radiation exposure was demonstrated in the RAD-Matrix trial (20). Moreover, a strong correlation between procedural DAP and reference personal dosimeter dose was demonstrated by Sailer et al (24). Furthermore, Brasselet et al (25) and Kuipers et al (26) revealed strong correlations between patient and operator exposure.…”
Section: Discussionmentioning
confidence: 85%
“…Recently, in the medical field, with the development of preventive medicine, the number of tests using medical radiation has increased significantly; hence, exposure to medical radiation is also increasing 15 . There are three factors for radiation defense: time, distance, and shielding, but active shielding is the best way for protecting healthcare professionals working with patients 16 .…”
Section: Discussionmentioning
confidence: 99%